Antimutagenic Activity of The Methanol Extract of Helichrysum plicatum ssp. plicatum - OZBEK, TULIN; GULLUCE, MEDINE; ADIGUZEL, AHMET; OZKAN, HAKAN; SAHIN, FIKRETTIN; ORHAN, FURKAN (Asian Journal of Chemistry, 2010)
The present study was conducted to evaluate the antimutagenic activity of methanol extract of Helichrysum plicatum ssp. plicatum plants. Antimutagenic activity of the extract was estimated by employing AMES- Salmonella/microsome assay by using Salmonella typhimurium TA1535 and TA1538 strains against direct acting mutagens sodium azide (NaN3), 4-nitro-1-quinoline oxide and the S9-dependent mutagen 2-amino fluorene (2AF). In this study, standard plate incorporation method was preferred to determine antimutagenic activity. In the absence of S9 metabolic activation all three doses of plant extract showed statistically significant (p < 0.05) antimutagenic activity on TA1535 strain, but no on the TA1538 strain. In the presence of S9 microsomal fraction, plant extract exerted moderate antimutagenic activity against the 2AF mutagen and reduced mutant colonies in the TA1535 and TA1538 strains. The present results indicate that H. plicatum ssp. plicatum extract has antimutagenic activity.